If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -6 = 9x + 14 Reorder the terms: -6 + 13x = 9x + 14 Reorder the terms: -6 + 13x = 14 + 9x Solving -6 + 13x = 14 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -6 + 13x + -9x = 14 + 9x + -9x Combine like terms: 13x + -9x = 4x -6 + 4x = 14 + 9x + -9x Combine like terms: 9x + -9x = 0 -6 + 4x = 14 + 0 -6 + 4x = 14 Add '6' to each side of the equation. -6 + 6 + 4x = 14 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = 14 + 6 4x = 14 + 6 Combine like terms: 14 + 6 = 20 4x = 20 Divide each side by '4'. x = 5 Simplifying x = 5
| 3x+10+40= | | 10x/y | | -3(-7+m)= | | 3x-5=137 | | 17x=5y+1 | | -4a^2-45a-50=0 | | x+48=x | | 8v+13=3v+18 | | 3x+40+10=180 | | 6(2x+4)=3(8+4x) | | x^-3/2=0 | | 6x-5y+3=-27 | | 9cot^2x+1=4 | | X^3-4x^2-14x-60=0 | | 3x+10+40=360 | | 9=3p+6 | | 8b-13b= | | 9cot^2x=4 | | x+4+2x=137 | | 11s+12t=93 | | P=275/12i1714 | | 7w+4=5w-10 | | 6(2Y+2)-9=3 | | 1-7x=6x-129 | | 2(T-2)+9=-9 | | 5(3x-1)=-10x+20 | | 6/(2/3) | | 9(5n+4)= | | 5p+6q=54 | | 3/5y-6/5=4 | | 2p+3q=24 | | 3x(x+1)-x(3x+1)=x-7 |